Screening for Antimicrobial Activity of Nine Ethanolic Extracts Obtained from Leaves of Begonia Plant: a Possible Alternative in the Treatment of Infections Caused by Citrobacter freundii - Buyun, Lyudmyla; Tkachenko, Halyna; Kurhaluk, Natalia; Góralczyk, Anna; Tomin, Vładimir; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Many plants of the family Begoniaceae are used in the treatment of different diseases. Traditionally leaves of Begonia L. are used to decrease of fleeting pain in the limbs and joints, for blood purification, to reduce the body temperature, for treating anemia, for the treatment of respiratory infections, diarrhea, blood cancer, and skin diseases, peptic ulcer, conjunctivitis, colic and dyspepsia, dysentery and mouth ulcer. Moreover, the leaves of Begonia species are used for the treatment of cancer; besides, they possess anti-HIV activity. Some of the plants of the genus Begonia were previously reported for their antimicrobial activities. The antimicrobial activity of ethanolic extracts obtained from the leaves of Begonia solimutata L.B. Sm. & Wassh., Begonia goegoensis N.E.Br., Begonia foliosa Kunth, Begonia × erythrophylla Hérincq, Begonia thiemei C.DC., Begonia peltata Otto & Dietr., Begonia heracleifolia Cham. & Schltdl., Begonia dregei Otto & Dietr., and Begonia mexicana G. Karst. ex Fotsch was evaluated against the clinical strain of Citrobacter freundii strain. The testing of the antibacterial activity of the plant extracts was carried out in vitro by the Kirby-Bauer disc diffusion technique. All ethanolic extracts obtained from leaves of Begonia species exhibited high activity against C. freundii. The most effective plants among species screened against Citrobacter freundii locally isolated were B. thiemei, B. foliosa, and Begonia × erythrophylla being highly active with the ethanolic extract (diameters of inhibition zone were ranged from 16.5 to 26 mm). The highly active antimicrobial effects of extracts obtained from B. thiemei, B. foliosa noted against Citrobacter freundii are worthy of highlighting. The identification of active compounds and their mode of action requires further investigation for antibacterial drug development